2020
DOI: 10.3390/ijms21031172
|View full text |Cite
|
Sign up to set email alerts
|

Transposon Insertion Mutagenesis in Mice for Modeling Human Cancers: Critical Insights Gained and New Opportunities

Abstract: Transposon mutagenesis has been used to model many types of human cancer in mice, leading to the discovery of novel cancer genes and insights into the mechanism of tumorigenesis. For this review, we identified over twenty types of human cancer that have been modeled in the mouse using Sleeping Beauty and piggyBac transposon insertion mutagenesis. We examine several specific biological insights that have been gained and describe opportunities for continued research. Specifically, we review studies with a focus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 157 publications
(127 reference statements)
0
14
0
Order By: Relevance
“…Therefore, choosing the right system for the right application is essential. For example, the preferential integration of Tol2 and PB into TSSs is advantageous for promoter/enhancer trapping [ 108 , 159 ], while the close-to-random insertion profile of SB enables to perform highly unbiased screens and detection of features that would be unlikely reached with other methods [ 160 ]. As discussed in previous sections, PB was shown to be highly active in a variety of species from yeast to humans, a property that makes it an almost universal tool for mutagenesis screens [ 161 , 162 ].…”
Section: Basic Research Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, choosing the right system for the right application is essential. For example, the preferential integration of Tol2 and PB into TSSs is advantageous for promoter/enhancer trapping [ 108 , 159 ], while the close-to-random insertion profile of SB enables to perform highly unbiased screens and detection of features that would be unlikely reached with other methods [ 160 ]. As discussed in previous sections, PB was shown to be highly active in a variety of species from yeast to humans, a property that makes it an almost universal tool for mutagenesis screens [ 161 , 162 ].…”
Section: Basic Research Applicationsmentioning
confidence: 99%
“…Tol2 enabled mutagenic screens in this model [ 159 , 163 ], and remains a major tool in zebrafish research [ 165 ]. Transposon-based screens are also currently of particular interest in cancer research to identify oncogenes, drivers of metastasis and predictors of therapy resistance [ 160 ]. As high-throughput technologies are increasingly accessible and discoveries require more data and efforts, we predict that transposon-based mutagenic screens will play a major role in unraveling the remaining mysteries present within genomic DNA.…”
Section: Basic Research Applicationsmentioning
confidence: 99%
“…Noorani et al [67] demonstrated, by means of PiggyBac mutagenesis [68] and exome sequencing, the targets of EGFR amplification or EGFRvIII in gliomas. HDAC6 was not among those targets.…”
Section: Hdac6 Silencing In Glioblastoma Cell Linesmentioning
confidence: 99%
“…It is therefore unclear how our results might translate into an in vivo setting. Although we do not include in vivo experiments, testing HDAC6 knock-down in mouse experiments in future studies is important, e.g., using mouse models of glioblastoma as those recently reviewed by Noorani [73], who discusses on more faithful mouse models resembling human gliomas, including new cre/LoxP transgenic lines that allow more accurate cell targeting of genetic recombination, Sleeping Beauty [74], and PiggyBac transposons [68] for the integration of transgenes and genetic screens and CRISPR-cas9 [75] for generating genetic knockout and functional screens. Applications of these technologies are providing novel insights into the functional genetic drivers of gliomagenesis, how these genes cooperate with one another, and the potential cells-of-origin of gliomas, knowledge of which is critical to the development of targeted treatments for patients in the clinic [73].…”
Section: Hdac6 Silencing In Glioblastoma Cell Linesmentioning
confidence: 99%
“…In later screens, Cre-inducible SB or PB transposase was used to restrict transposon mutagenesis to specific tissues such as B-cells, liver, and the gastrointestinal tract [82][83][84]. In addition, transposon screens were employed to find drivers of many other tumor types including breast, lung, prostate, thyroid, melanoma, and medulloblastoma (reviewed in [85][86][87]). Together, these studies showed that transposon mutagenesis can drive tumorigenesis in wild type or genetically-predisposed backgrounds.…”
Section: Transposon Mutagenesis Screensmentioning
confidence: 99%